Private International Law Aspects of Authors’ Contracts: The Dutch and French Examples - Ginsburg, Jane C.; Sirinelli, Pierre (The Columbia Journal of Law & the Arts, 2016)
Copyright generally vests in the author, the human creator of the work. But because, at least until recently, most authors have been ill-equipped to commercialize and disseminate their works on their own, the author has granted rights to intermediaries to market her works. Since most authors are the weaker parties to publishing, production, or distribution contracts, the resulting deal may favor the interests of the intermediary to the detriment of the author’s interests. Many national copyright laws have introduced a variety of corrective measures, from the very first copyright act, the 1710 British Statute of Anne, which instituted the author’s reversion right (still in force, albeit much modified, in U.S. copyright law), to detailed limitations on the form and scope of grants found in many continental European copyright laws. Recently, the Netherlands and France have amended their copyright laws to reinforce author-protective provisions; the French reforms particularly envision the publishing contract in the digital environment. But many author contracts, especially in the digital environment, grant rights for multiple territories: how does the international dimension of these agreements affect the practical ability of individual countries to regulate authors’ contracts with respect to exploitations occurring within their borders? If, on the one hand, “lawmakers tend to be provincial in developing copyright-contract rules, remaining focused on largely local parties and interests rather than on policies common to many jurisdictions,” and, on the other, general principles of private international law leave to the parties the determination of the law applicable to their contract, may the parties simply avoid “provincial” protections of authors’ economic interests by choosing (or the stronger party imposing) the law of a less author-interventionist jurisdiction to govern the full territorial extent of the ransfer? This Article will first discuss two examples of reforms of copyright-contract law, then will consider the extent to which private international law rules may render these reforms largely ineffective for authors who grant rights for multiple territories. Finally, we will propose private international law approaches that preserve local author-protective contract restrictions without rendering the implementation of the international agreement unduly cumbersome or unpredictable. We recognize that our approach departs from classic, content- neutral, private international law rules, because it seeks to impose a particular outcome. But content-neutral choice of law rules are what create the problem that provoked this examination in the first place: the rule of “party autonomy,” that directs courts to look to the law the parties choose for their contract enables the stronger party to avoid weaker party protections simply by submitting the contract to a less-constraining national law. The proposed rule remains within the general private international law (nonsubstantive) framework because it in no way instructs states to adopt author-protective measures. It simply endeavors to ensure, if a state does determine to recalibrate the balance of power between authors and exploiters, that the contract not set the state’s efforts to protect its resident authors to naught.